Liver metastasis affects progression pattern during immune checkpoint inhibitors monotherapy in gastric cancer - Motoo, Iori; Ando, Takayuki; Hamashima, Takeru; Kajiura, Shinya; Sakumura, Miho; Ueda, Yuko; Murayama, Aiko; Ogawa, Kohei; Tsukada, Kenichiro; Ueda, Akira; Suzuki, Nobuhiro; Nakada, Naokatsu; et al. (Frontiers in Oncology, 2023)
Introduction The efficacy of immune checkpoint inhibitors (ICIs) is heterogeneous at each metastatic site, and tumor progression pattern is associated with survival; however, it remains unclear in gastric cancer (GC). Therefore, we aimed to clarify the progression pattern in response to ICIs in patients with GC, and we analyzed its mechanism focusing on the intratumoral immune cells. Methods Patients who received ICIs were retrospectively classified into non-systemic and systemic progression groups based on their radiological assessments. Moreover, the best percentage change in target lesions from each organ was compared. Results Among 148 patients, the non-systemic progression group showed a significant improvement in overall survival (OS) compared with the systemic progression group (median, 5.6 months vs. 3.3 months; HR, 0.53; 95%CI, 0.32–0.89; p = 0.012). Poor performance status (HR, 1.73, 95%CI, 1.00–2.87) and systemic progression (HR, 3.09, 95%CI, 1.95–4.82) were associated with OS. Of all metastatic sites, the liver showed the poorest percentage change, and liver metastasis (OR, 2.99, 95%CI, 1.04–8.58) was associated with systemic progression. Hence, intratumoral CD8+ T-cell density was lower in patients with liver metastasis than in those without liver metastasis after ICIs, although the density of CD4+ T-cells (Th1, Th17, and Treg) and CD163+ cells (TAM) were not significantly different. Conclusion The new progression pattern was associated with OS in GC. Liver metastasis may be a predictive factor of systemic progression during ICIs by regulating intratumoral CD8+ T-cells.